Heavy Metal Sensing Using Self‐Assembled Nanoparticles at a Liquid–Liquid Interface. Issue 10 (24th July 2014) - Cecchini, Michael P.; Turek, Vladimir A.; Demetriadou, Angela; Britovsek, George; Welton, Tom; Kornyshev, Alexei A.; Wilton‐Ely, James D. E. T.; Edel, Joshua B.
<x xml:space="preserve">Abstract</x> A novel sensor for the detection of heavy metal ions in solution has been designed. It uses a recently developed new nanoplasmonic platform based on self‐assembled layers of Au nanoparticles (NPs) at a liquid–liquid interface (LLI). This system is shown to be very promising for the detection of trace amounts of analyte molecules through their Raman scattering fingerprints, enhanced by the NPs' localized plasmonic resonances. For the detection of heavy metals this platform is modified by controlling and optimizing the ligand functionality on the NPs through the use of polyaromatic ligands (PALs). Importantly, the PALs are soluble in the organic phase whilst the NPs and heavy metals are soluble in the aqueous phase; therefore the self‐assembly at the LLI is key to efficient detection. For example, the system described here is able to detect Hg(II) quantities down to 10 pmole levels whilst at the same time differentiating between other heavy metals based on spectral variability. Finally, airborne mercury detection is shown to be possible with a minimally modified platform at the air‐liquid/air‐solid interface, with a clearly resolvable mercury‐positive spectrum being observed within 5 min of exposure.